EDUKASI PENTINGNYA BAHASA INGGRIS DI ERA GLOBALISASI - Mika Andika Mika; Nova Mardiana (Universitas Majalengka, 2023)
Abstract The era of globalization or also known as the free market requires every individual to be able to compete for reliable resources. Seeing that the role of English is indispensable, mastery of English should be an individual investment so that a brilliant life is achieved. But in fact, there are still many students, especially EFL Learners, who have difficulty understanding English due to a lack of practice in their daily lives. The objectives to be achieved are: Providing them with an understanding of the importance of mastering English in the era of globalization and providing opportunities to be able to take part in English language training. Research method: activities were carried out at MTs Negeri 02 Bangka, on Thursday, November 24th, 2022 which was attended by 47 students. The activity began with introductions, opening, pre-test, counseling about the importance of English, delivery of material, demonstrations, post-tests, closing, and group photos. Results: the pretest results showed that 2 out of 5 children liked English and were able to answer questions about: the expression of pain. However, after the extension activities were carried out, all students were motivated to learn English and were able to answer the questions given. This shows that there is an increase in their understanding after being given counseling. Results: the pretest results showed that 2 out of 5 children liked English and were able to answer questions about: the expression of pain. However, after the extension activities were carried out, all students were motivated to learn English and were able to answer the questions given. This shows that there is an increase in their understanding after being given counseling. Results and conclusions: the pretest results showed that 2 out of 5 students liked English and were able to answer questions about: the expression of pain. However, after the extension activities were carried out, all students were motivated to learn English and were able to answer the questions given. This shows that there is an increase in their understanding after being given counseling.